A Ring‐Opening Metathesis Polymerization Catalyst That Exhibits Redox‐Switchable Monomer Selectivities. Issue 25 (3rd February 2017) - Lastovickova, Dominika N.; Shao, Huiling; Lu, Gang; Liu, Peng; Bielawski, Christopher W.
Abstract: A ring‐opening metathesis polymerization catalyst supported by a redox‐active N ‐heterocyclic carbene was synthesized and found to undergo reversible reduction. In its neutral form, the catalyst polymerized 1, 5‐ cis, cis ‐cyclooctadiene at a higher rate than that of a norbornene derivative; however, upon reduction, the selectivity was found to reverse. Utilizing this oxidation state dependent selectivity, a series of copolymers with controlled compositions, microstructures, and physical properties were prepared by redox‐switching the catalyst over the course of a series of polymerization reactions. Abstract : I choose you ! A redox‐switchable analogue of the Grubbs third‐generation catalyst was shown to selectively polymerize certain monomers within various mixtures depending on the oxidation state of the redox‐active ligand.